THE CORRELATION BETWEEN MOTIVATION AND SPEAKING ABILITY - Aidil Syah Putra (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
The aim of the research is to know the correlation between motivation and speaking ability at eighth grade students of SMPN 17 Tangerang. To collect and analyze the data, the researcher used the simple speaking test and questionnaire in order to support the data collected. The result of this research showed that there was improvement on the students’ speaking ability through motivation. It can be seen on the students’ speaking score which had reached the score of Minimum Mastery Criterion-Kriteria Ketuntasan Minimal (KKM). In addition, the students’ score of motivation in learning speaking showed significant improvement. The average of the students’ score in learning speaking was 74.75 and the average of the students’ score of motivation was 77.62. It means that the students have high motivation in learning speaking. From the evidence above, the researcher conclude that there was positive correlation through motivation way in teaching speaking ability. The students more active in the class and the students more interested in developing speaking ability through motivation. As suggestion, the researcher hopes that the teachers have to be able to choose appropriate way or technique in teaching English.